A protocol for prospective studies of 25-hydroxyvitamin D, leptin and body mass index in relation to cutaneous melanoma incidence and survival. Issue 6 (21st June 2017) - Stenehjem, Jo Steinson; Grimsrud, Tom K; Rees, Judith R; Vos, Linda; Babigumira, Ronnie; Veierød, Marit B; Robsahm, Trude Eid
Abstract : Introduction: The incidence and mortality rates of cutaneous melanoma (CM) are increasing among fair-skinned populations worldwide. Ultraviolet radiation (UVR) is the principal risk factor for CM, but is also the main source of 25-hydroxyvitamin D (25(OH)D), which has been associated with reduced risk and better prognosis of some cancer types. However, both low and high 25(OH)D levels have been associated with increased risk of CM. Obesity as measured by body mass index (BMI) is associated with risk of several cancers and has also been suggested as a risk factor for CM, and may also be related to insufficient 25(OH)D and/or high leptin levels. Moreover, contracting a CM diagnosis has been associated with increased risk of developing second cancer. We aim to study whether low prediagnostic serum levels of 25(OH)D, high prediagnostic levels of BMI and high serum leptin levels influence CM incidence, Breslow thickness and CM mortality, and risk of second cancer and survival after a CM diagnosis. Methods and analysis: Cohort and nested case–control studies will be carried out using the population-based Janus Serum Bank Cohort (archival prediagnostic sera, BMI, smoking and physical activity), with follow-up from 1972 to 2014. Additional data will be received from the Cancer Registry of Norway, the national Cause of Death Registry, Statistics Norway (education and occupation) and exposure matrices of UVR. Time-to-event regression models will be used to analyse the cohort data, while the nested case–control studies will be analysed by conditional logistic regression. A multilevel approach will be applied when incorporating group-level data. Ethics and dissemination: The project is approved by the Regional Committee for Medical Research Ethics and is funded by the Norwegian Cancer Society. Results will be published in peer-reviewed journals, at scientific conferences and in the news media.